Location of the placenta by auscultation with doppler - Sánchez, Hugo (2015)
The ultrasound has solved the problem of the placentae localization, Still the high cost of ecography attempts its massification. But in this technique we count with equipments that taking advantage of the. Doppler effect inolate the acoustic reflection with notable economic advantage and simplicity in its management that also permits its high diffusion. In the beginning Doppler was used to get cardiac sound of the fetus. Besides this sound, we can appreciate others with this instrument where the placentae blow is an important one. While getting it, we supposed that it was possible to delimit the placentae contour which projection was drawn on the abdominal wall by "map out". The investigation has been taken in the Hospital Docente of Trujillo in a group of 50 pregnants that for got surgical interventions.